A new neutron depth profiling spectrometer at the JCNS for a focused neutron beam. Issue 3 (3rd March 2020) - Vezhlev, E.; Ioffe, A.; Mattauch, S.; Staringer, S.; Ossovyi, V.; Felder, Ch.; Hüger, E.; Vacik, J.; Tomandl, I.; Hnatowicz, V.; Chen, C.; Notten, P.H.L.; et al.
Abstract : A new neutron depth profiling (NDP) spectrometer has been designed and built for the use at a high intensity focused cold neutron beam of the reflectometer MARIA at the Heinz Maier-Leibnitz Zentrum (MLZ, Germany). The extremely high neutron flux at the sample position of MARIA joined with the multiple charged particle detectors allows less than 10 s sampling rate and paves the way to study the kinetics of Li ions in thin-film microbatteries. The performance of the spectrometer with standard calibration samples and L i N b O 3 amorphous thin films is presented; possibilities to operando study the Li distribution inside thin-film rechargeable lithium batteries are discussed.